Gen Z and Interpersonal Conflict Management: (A Phenomenological Study of Communication Science Students at Dharmawangsa University) - Siregar, Rafiqah Yusna; Lumbantoruan, Rachel Mia Lorenza; Hamzah, A. Hadian Pratama (CONTENT: Journal of Communication Studies, 2025)
The study aims to describe how Gen Z students at Dharmawangsa University especially those in the communications science program, manage interpersonal conflicts based on their personal experiences. This study uses a phenomenological paradigm through their experiences in managing project assignments in 3 months and divided into several groups. During 3 months of working on the project, several groups of students found various problems that then required them to carry out conflict management according to the personal characteristics of each member in each group. This research uses a qualitative method with a descriptive research design with the Miles and Huberman analysist techniques, including data reduction, data display and conclusions. Meanwhile, data collection techniques are carried out in 3 stages, observation, interview, and documentation. The result shows that Gen Z is exemplified by two interpersonal conflict management strategies: avoiding conflict and compromising, both of which involve a variety of techniques. Making concessions involves being transparent with all parties involved, having in-depth conversations, negotiating, determining the root cause of the disagreement, and refraining from blaming the other party. For Gen Z, this is considered a positive self-concept. Meanwhile, giving in, doing what others ask, and acting as if you are unaware of the problem are ways to avoid interpersonal conflict. This demonstrates a loose and uncaring mindset, which are two negative self-concept characteristics. Thus, the results of this study will increase understanding, knowledge, or concepts regarding the characteristics of Gen Z in interpersonal conflict management.